Wives of 19th century deportees as organisers of family life in Siberia - Jędrychowska, Barbara (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
19th century deportations to Siberia have been one of the most painful experiences of Poles of that age and they are a permanent element of Polish history. Mostly due to the literature of Polish Romanticism, and then also of visual art, the lives of trans-Uralian exiles has for a long time been presented only in the context of martyrdom. It was the Polish Sybiraks, returning to the homeland after many years, who have themselves changed this image. In their testimonies (memoirs, diaries, journals, letters) published back in the 19th century, one can find interesting descriptions not only of everyday struggles with the difficult reality of the deportation but also about functioning in the community of deportees and their families.
Keywords: 19th century; Siberia; deportations; wives of deportees